Unilateral baseball pitching: morphological and functional adaptations in the neck muscles - Leila Rahnama; Ceren Acik; Christine Dy; Stefan Keslacy (Frontiers in Sports and Active Living)
BackgroundFunctional asymmetry and muscle imbalances are recognized as contributors to injury risk in athletes. Sports with repetitive unilateral movements such as baseball pitching can lead to adaptations in shoulder and scapular muscles. There is a lack of research on whether these movements result in neck muscle alterations. Understanding potential asymmetries in neck musculature could provide valuable insights into athletes’ performance and injury prevention strategies.MethodsA total of 14 collegiate baseball pitchers and 15 controls voluntarily participated in this study. Bilateral dorsal neck muscle thickness, stiffness, neck range of motion (ROM), neck repositioning error, and extensor strength were measured, and the asymmetry between the two groups was compared. Rehabilitative ultrasound imaging was used to assess muscle thickness and stiffness. An inclinometer and a dynamometer were utilized to evaluate neck ROM and strength, respectively.ResultsThe mean age of the baseball pitchers and controls was 21.86 ± 1.6 and 25.87 ± 5.10 years, respectively. A significantly greater thickness of the splenius capitis on the non-dominant side was observed in baseball pitchers [p = 0.029, effect size (ES) = 0.857], whereas controls demonstrated symmetrical muscle thickness in all dorsal neck muscles. Pitchers exhibited higher neck extensor maximal voluntary contraction compared to controls (p = 0.017, ES = 0.926). Controls showed more bilateral differences in muscle stiffness in the splenius capitis and the semispinalis cervicis, although statistical asymmetry was not demonstrated.ConclusionThe cervical multifidus muscles showed bilateral symmetry despite the unilateral throwing motion in baseball pitching. However, unilateral neck rotation toward the non-dominant side appears to contribute to greater thickness of the splenius capitis on the non-dominant side of pitchers.